Implementation of a New Torque and Flux Controllers for Direct Torque Control (DTC) of Induction Machine Utilizing Digital Signal Processor (DSP) and Field Programmable Gate Arrays (FPGA) - Toh, C. L. (IEEE, 2005)
This paper presents the simulation and experimental results of a new torque and flux controllers for the direct torque control (DTC) of induction motor drives. The controllers provide a simple solution to the variable switching frequency and high torque ripples problems encountered in the hysteresis-based DTC drives. The controllers operate based on the comparison between the compensated error signals and the triangular waveforms. Implementation of these controllers using the combination of a digital signal processor (DSP) and a field programmable gate array (FPGA) device is presented. The simulation and experimental results showed that the controllers were capable of reducing the torque and flux ripples significantly. At the same time the switching frequency was fixed, independent of the operating conditions.